Exploring the presence of multiple abnormal non-motor features in patients with cervical dystonia. (December 2021) - Naik, Aaditi G.; Ezana, David; Cannard, Grace; Mitchell, Nia; Tomaras, Miranda; Meystedt, Jacqueline C.; Sayce, Lea; Charles, David; Hacker, Mallory L.
Highlights: 80% of cervical dystonia (CD) patients had at least one abnormal non-motor feature. Only 20% of healthy control subjects demonstrated one abnormal non-motor feature. One-third of CD patients displayed two or more abnormal non-motor features. 80% of patients with cervical dystonia reported using a sensory trick. Non-motor feature testing could be a highly specific diagnostic tool for CD. Abstract: This study's aim was to investigate prevalence of four non-motor symptoms in patients with cervical dystonia and healthy controls to explore whether the presence of multiple non-motor features is associated with cervical dystonia diagnosis. Fifteen patients with cervical dystonia and 15 healthy controls underwent non-invasive testing of spatial discrimination threshold, temporal discrimination threshold, vibration-induced illusion of movement, and kinesthesia. All spatial discrimination threshold, temporal discrimination threshold, and vibration-induced illusion of movement measures were converted to standardized Z scores with scores >2.0 considered abnormal. Any incorrect kinesthesia response was considered abnormal. Prevalence of each abnormal non-motor feature was compared between groups using a chi-squared test. A higher proportion of patients with cervical dystonia had abnormal spatial discrimination threshold ( p  = 0.01) and abnormal kinesthesia ( p  = 0.03) scores compared to healthy control subjects. There were no significant differences between the proportion of patients with cervical dystonia versus healthy controls for abnormal temporal discrimination threshold ( p  = 0.07) or abnormal vibration-induced illusion of movement ( p  = 0.14). Forty-seven percent of patients with cervical dystonia (7/15) demonstrated one abnormal non-motor feature, 20% (3/15) displayed two abnormal features, and 13% (2/15) displayed three abnormal features. Kinesthesia was the only non-motor feature identified as abnormal in the control group (20%, 3/15). All four tests demonstrated high specificity (80–100%) and low-moderate sensitivity (13–60%). These findings suggest that non-motor feature testing, specifically for spatial discrimination threshold and kinesthesia, could be a highly specific diagnostic tool to inform cervical dystonia diagnosis. Further investigation is needed to confirm these findings.